KARAKTERISTIK DAN PEMERIKSAAN RAPID TES ANTIBODI COVID-19 PADA IBU HAMIL DI PUSKESMAS WILAYAH MARTAPURA - Dinna Rakhmina; Aina Nurvita Sari; Ratih Dewi Dwiyanti (Husada Mahakam, 2021)
Wuhan, China was the place where the first cases of Covid-19 were found, and 118 pregnant women with COVID-19 were identified from 50 hospitals throughout the city of Wuhan from December 2019 – March 2020. The purpose of this study was to find out the description of the Covid-19 examination in pregnant women at Puskesmas Martapura City. A descriptive survey is conducted using a cross-sectional design. All pregnant women in their third trimester who had a rapid test for Covid-19 antibodies performed at the Puskesmas Martapura City and samples taken utilizing a full sampling approach were included in this study. The study's conclusions were mostly based on their age (20-35 years) 14 individuals (70%), senior high school 12 people (60%), housewives 18 people (90%), and knowledge level (100%). The results showed that 131 people were reactive and 957 were non-reactive in the antibody rapid test examination for pregnant women in their third trimester from June 2020 to March 2021. According to the findings, 12.04% of pregnant women in their third trimester are reactive, whereas 87.96% are non-reactive. Suggestions to the public on how to better understand clinical symptoms, mechanisms of transmission, and Covid-19 prevention efforts in order to encourage good lifestyle choices. This research can be continued by observing the severity of Covid-19 symptoms in pregnant women who are infected and the effect of pregnant women infected with Covid-19 on babies born. Keywords: Covid-19, Antibody rapid test, Pregnant woman